Nutritional profile in Indonesian elderly subpopulation - Deasy Irawati; Ardiana Ekawanti; Anom Josafat (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2020)
Background: Data on malnutrition in the developing countries showed that 1–3 elderly in every 5 elderly were malnourished. However, the data in Indonesia were limited. Malnutrition in elderly is often underdiagnosed and thus it usually goes undetected at earlier stage.Objective: The aim of this study was to examine nutritional profile of elderly by using several indicators: anthropometry, Mini Nutritional Assessment (MNA) Questionnaire, and dietary intake.Methods: A cross-sectional study was conducted among community dwelling elderly (aged =60 years) and elderly in the institutional care. The outcome variables were prevalency of malnutrition (undernutrition and overnutrition) and macro and micronutrient intake. Nutrition profiles were assessed using anthropometry, MNA and 24-hour food recalls. Comparative analysis between continuous variables was conducted using Mann-Whitney or ANOVA. Differences between categorical variables were assessed using Chi-square tests or Fisher’s exact test.Results: Based on BMI, in total, 1 in 2 elderly was either undernutrition or overnutrition. Based on MNA, 1 in 2 elderly were malnourished or at risk of malnutrition. Place of residency and gender were associated with the distribution of malnutrition in elderly (p<0.001). Approximately 1 in 2 elderly from the community dwelling group were overweight and obese whereas 1 in 3 elderly from the institutional care group were severely thin and thin. The intakes of 4 in 5 elderly were deficient in vitamin D, calcium, vitamin E and folate.Conclusion: Elderly in our population group were experiencing the double burden of malnutrition and this coexisted with micronutrient deficiency.